Efeito da vitamina 25(OH) D sobre a expressão de receptor toll-like e mediadores inflamatórios em monócitos frente ao ambiente urêmico - Brito, Rodrigo Barbosa de Oliveira (2017)
The chronic kidney disease (CRD) is characterized by an inflammatory condition caused by the presence of uremic toxins in the patients plasma. This inflammatory state is associated with a high risk of cardiovascular diseases and infections. In CKD, there is a deficiency of vitamin 25 (OH) D, which has immunomodulatory properties, and the supplementation with it can decrease inflammation present in uremia. The aim of this study was to evaluate the effect of 25 (OH) D on inflammatory pathways such as toll like receptor 4 (TRL4), oxidative stress (ROS) and expression of vitamin D receptor (VDR), 1-α hydroxylase, 24 hydroxylase And inflammatory mediators in monocytes in the uremic environment. The human monocytes (U937 lineage) were treated with or without 25 (OH) D 50ng / ml for 24 hours, then they were incubated with 50% serum from healthy patients or uremic patient serum for 24 hours at 37 ° C and 5% CO2. Monocytes were characterized by the expression of CD14 +. TRL4, VDR, CYP24, Cyp27 and ROS were evaluated by flow cytometry. Cell culture supernatant ELISA was performed for IL-6, TNF-α, IL-10, catatelicidin, MCP-1 and NF-KB. We observed a high expression of TRL-4, IL-6, TNF-α, IL-10, cathelicidin and MCP-1 in monocytes incubated with uremic serum, compared when incubated with healthy serum. Treatment with 25 (OH) D was able to reduce the expression of TRL4, cathelicidin and MCP-1 against the uremic environment. There was no difference in the expression of VDR, CYP27 and CYP24 enzymes and NF-KB. We conclude that the uremic environment induces inflammation, increasing TRL4 and inflammatory mediators, treatment with vitamin D induces an improvement in the inflammatory parameters, resulting in less inflammation in the uremic environment.